Non-CO2 greenhouse gas separation using advanced porous materials - Yan-Long, Zhao; Zhang, Xin; Mu-Zi Li; Jian-Rong, Li (Chemical Society reviews, 2024)
Global warming has become a growing concern over decades, prompting numerous research endeavours to reduce the carbon dioxide (CO2) emission, the major greenhouse gas (GHG). However, the contribution of other non-CO2 GHGs including methane (CH4), nitrous oxide (N2O), fluorocarbons, perfluorinated gases, etc. should not be overlooked, due to their high global warming potential and environmental hazards. In order to reduce the emission of non-CO2 GHGs, advanced separation technologies with high efficiency and low energy consumption such as adsorptive separation or membrane separation are highly desirable. Advanced porous materials (APMs) including metal–organic frameworks (MOFs), covalent organic frameworks (COFs), hydrogen-bonded organic frameworks (HOFs), porous organic polymers (POPs), etc. have been developed to boost the adsorptive and membrane separation, due to their tunable pore structure and surface functionality. This review summarizes the progress of APM adsorbents and membranes for non-CO2 GHG separation. The material design and fabrication strategies, along with the molecular-level separation mechanisms are discussed. Besides, the state-of-the-art separation performance and challenges of various APM materials towards each type of non-CO2 GHG are analyzed, offering insightful guidance for future research. Moreover, practical industrial challenges and opportunities from the aspect of engineering are also discussed, to facilitate the industrial implementation of APMs for non-CO2 GHG separation.